La celeridad en los procesos de adopción en el Ecuador durante el año 2022 - Castillo Alvarez, Melva Alejandra (2024)
The purpose of this curricular integration work entitled “The relationship between adoption processes and the principle of celerity in Ecuador during the year 2022” is to analyze the adoption processes of minors in the country and their relationship with the principle of celerity. Evidently, this principle is not currently being complied with, causing an unnecessary delay at the moment of guaranteeing the right to a family and family coexistence of the minor, influencing the integral development of the child or adolescent. Consequently, the best interests of the child is compromised, in addition to causing possible adoptive parents to desist from the process. Therefore, to concretely reflect the proposed objectives, a methodology was applied to strengthen the research. It is focused on the application of empirical, descriptive, inductive, deductive, analytical, exegetical, comparative, historical, and statistical methods. Furthermore, a mixed approach was used based on the development of a descriptive type of research, with a cross-sectional design. In this research work, the techniques of documentary theoretical collection, documentary observation, survey, and interview were applied as well as it was done an analysis of adoption case files that have successfully completed the entire process. Through these techniques, various perspectives from doctrinarians, juridical experts as well as professionals in law, and individuals involved in the issue were collected which were reflected in the results and allowed to reach the following conclusion. It is necessary and indispensable that the principle of celerity be applied in all stages of the adoption process. This is to guarantee the best interests of the child and to avoid the violation of the right to have a family and family coexistence for all those children or adolescents who are in foster homes and long for parents who care about their integral development.